Teaching health science students during COVID-19: Cross-hemisphere reflections - McGill, Megann; Turrietta, Christina; Lal, Aparna (Journal of University Teaching and Learning Practice, 2021)
Efforts to mitigate the spread of the COVID-19 virus based on recommendations from government agencies across the world, such as physical distancing requirements, propelled university and college training programs into virtual learning environments in 2020. This unprecedented and largely unplanned shift to online/remote learning has led to novel pedagogical experiences for instructors, particularly those teaching in the field of health sciences, which typically rely on in-person and hands-on training to prepare students for their careers. Our manuscript aims to answer the research question, “What are the cross-cultural experiences of university instructors teaching students studying health sciences during a global pandemic?” The three authors of this manuscript are lecturers in higher education who teach in the health science programmes in different parts of the world (i.e., Australia, Pacific Northwest USA, Southwest USA). A reflective scholarship of teaching and learning method, collective autoethnographies, was used to examine the online/remote teaching experiences of the authors. Four shared themes emerged from our qualitative coding and reflective discussions, with our experiences highlighting the importance of human connection and comparisons to pre-pandemic teaching practice. Our reflections have implications for pedagogy and course design and highlight the limited support available for educators teaching during stressful times as we continue remote learning. These cross-cultural teaching experiences in health sciences provide important insights into cross-hemisphere discussions about teaching in a post-COVID world.